The Relationship of Energy Adequacy with Nutritional Status of Soccer Athletes of Indonesian Soccer Association - Fatinah Shahab; Syarifah Zahra; Aryu Candra (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: soccer is a sport that requires a high level of energy. The combination of training and adequate nutrition can make better sport performance. Nutritional status can determine the quality of athlete while competing and reducing the risk of illness and injury. Objective: This study aimed to determine the relationship between energy adequacy levels and the nutritional status of PSIS athletes. Methods: This correlational descriptive used a cross sectional design. Subjects were observed for a 2 months period. A total of 104 soccer athletes participated in thus study. The instrument of this research includes food recall and physical activity checklist for 3 x 24 hours, digital scale, Skinfold Caliper-Thickness and microtoise. Research variables include the level of energy adequacy, body mass index, and percent body fat. Results: The result showed that the energy adequacy level was 101 athletes (97.1%), normal nutritional status was 70 athletes (66.7%) and normal body fat percent was 71 (67.6%). The relationship between the level of energy adequacy and the percentage of body fat in PSIS athletes with a p-value of 0.56 (>0.05) and a correlation with an r value of 19%. The level of energy adequacy has a significant relationship with the percentage of body fat. Conclusion: it is recommended that dietary habit should be planned to improve the performance in sport fields.